Complications of Three Different Intravitreal Anti VEGF at Five Different Centers Observing Different Inravitreal Injection Protocols - Muhammad Qasim Lateef, Muhammad Tayyab, Hussain Ahmad Khaqan, Tariq Khan, Haroon Tayyab, Tariq khan Marwat (Pakistan Journal of Ophthalmology, 2019)
Purpose: To analyze the intra vitreal Anti VEGF complications observing different intravitreal injection protocols. Study Design: This is an open label, prospective, multicenter cohort study. Place and Duration of Study: The audit was conducted at five different hospitals from September 2016 to March 2018. Material and Methods: All intravitreal injections of Bevacizumab, Ranibizumab and Aflibercept were included irrespective of the context of the injections. Questions were asked in the designed proforma regarding use of povidone iodine, sterile drapes, Opsite, speculum, sterilized instruments, pre-operative and post-operative antibiotics. Data was also collected about scrubbing before the procedure, use of cap and mask during the procedure and whether injection was given in Operation Theater or in an office based setup. Complications, whether systemic or ocular, were enumerated and their management was also noted down. Results: A total of 2,854 injections were given to 2,289 patients by 10 different surgeons in 5 different institutes. There were 6 surgeons who did not prescribe pre-operative antibiotics, 4 surgeons did not use cap and mask during the procedure, while 2 surgeons did not use Opsite during the procedure. Office based injections were given by 1 surgeon while all the others administered injections in an operation theater. Complications included subconjunctival hemorrhage, in 184 cases, sterile inflammation in 78 cases, transient rise in IOP in 53 eyes and 1 case each of endophthalmitis, lens touch and retinal detachment. Conclusion: The ocular and systemic complications number is low and comparative to the available literature after injecting different intra-vitreal anti VEGF. Key words: Intravitreal injection, Anti-VEGF, Endophthalmitis, Bevacizumab, Ranibizumab, Aflibercept.